The Influence of the Digital Economy onto Social Relations Transformation - Kovalenko, Mykola; Sikalo, Maksym (Theory and Practice of Public Administration, 2023)
The article explores the influence of the digital economy on the transformation of social relations. Using a systematic approach, an axiological method, methods of analysis and synthesis, a logical method of reproduction of scientific knowledge of the development of social relations, aggregation of empirical data, the author found out that the development of digital technologies significantly affects the transformation of almost all components of social relations. The research results indicate that the digital economy is becoming a key component of digital transformation, which is determined mainly by economic processes and phenomena arising from the use of digital technologies at all stages of social reproduction, which gradually acquire a socio-economic dimension. This is accompanied by a slow abandonment of outdated technologies, the maintenance of which can be costly to the socio-economic system. There is also, the slow transformation of social ideas, values, norms, traditions and ideals, which forms the basis of the cultural and civilizational experience of society. A number of discovered advantages and opportunities provided by digital transformation are presented. However, the primary component of the digital transformation, which should lead to radical changes for the economy and various other social spheres, will not be so much the creation and use of digital technologies as a fundamental rethinking of the goals of society’s development, norms of behavior and ethical values of interpersonal relationships. The most expected consequences of digital transformation for society are related precisely to «transformation» as a deep, consistent restructuring of social processes. Today, digital transformation is penetrating all spheres of society at different rates, and these processes will only accelerate in the future. This becomes a certain driver of development, which ensures the identification and creation of new digital models of society, and can become a factor in the long-term cooperation of various groups of society for the sake of general well-being and common benefit. But the digital transformation of the socio-economic system at any level is a complex and lengthy process with long-term returns. It requires strategy, revision of societal models and processes, professional management, new infrastructure, new software, optimization of service mix, effective implementation mechanisms, training programs and reliable ongoing support. The spread of digital technologies in the economy and various social areas brings significant advantages, but also has potential threats and risks in various directions, which are highlighted in our research both from the point of view of micro- and macroeconomic approaches, and from the point of view of public administration. Prevention of the negative consequences of the use of digital technologies should include a system of measures capable of ensuring transparent rules and control over the collection, storage and analysis of large volumes of data about people’s personal lives, eliminating the risk of abuse and restrictions on personal freedom. It is important to prevent a situation where all social processes can become completely dependent on digital technologies and the Internet to such a large extent that it limits personal freedom, privacy and opportunities. And this is not only a possible loss of privacy due to monitoring of Internet activities, personal freedom due to control over information, but also the formation of psychological dependence on digital devices and services, the spread of digital autism and the «empty» hyperinformation environment. It is shown that the growth of digitalization increases the risks associated with the need to organize a powerful cyber security system. Data leaks, hacking attacks, and other cyber threats can have serious negative consequences for both personal freedom and privacy, as well as for ensuring national security based on the principles of protecting the public interest. The exploration of the influence of the digital economy onto social relations transformation showed that, in addition to focusing on increasing efficiency in various aspects, it is necessary to focus on other important things – increasing the protection of rights and freedoms, ensuring social welfare, improving the level of health care, increasing the level of security, protection national economic interests, providing wide access to quality education and culture, etc. For this purpose, the responsible, socially beneficial activity of public authorities, public organizations, political parties, and human rights organizations must be ensured, as well as active participation of citizens in the political and public life of society must be established.